2013
DOI: 10.1103/physrevlett.111.114801
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Coherent 19- and 38-nm Radiation at a Free-Electron Laser Directly Seeded at 38 nm

Abstract: Initiating the gain process in a free-electron laser (FEL) from an external highly coherent source of radiation is a promising way to improve the pulse properties such as temporal coherence and synchronization performance in time-resolved pump-probe experiments at FEL facilities, but this so-called "seeding" suffers from the lack of adequate sources at short wavelengths. We report on the first successful seeding at a wavelength as short as 38.2 nm, resulting in GW-level, coherent FEL radiation pulses at this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 38 publications
(48 reference statements)
0
43
0
Order By: Relevance
“…In this scheme, the FEL operates as a high-gain amplifier of the low-power HHG source, amplifying it by several orders of magnitude. Direct FEL seeding at 160 nm (Lambert et al, 2008), 61 nm (Togashi et al, 2011) and 38 nm (Ackermann et al, 2013) from HHG sources has been demonstrated in recent years. Limited by the ∼ 10 −6 conversion efficiency, however, present HHG sources typically have a cutoff wavelength around ∼20 nm due to their relatively low pulse energy.…”
Section: Generation Of Fully Coherent X-ray Pulsesmentioning
confidence: 99%
“…In this scheme, the FEL operates as a high-gain amplifier of the low-power HHG source, amplifying it by several orders of magnitude. Direct FEL seeding at 160 nm (Lambert et al, 2008), 61 nm (Togashi et al, 2011) and 38 nm (Ackermann et al, 2013) from HHG sources has been demonstrated in recent years. Limited by the ∼ 10 −6 conversion efficiency, however, present HHG sources typically have a cutoff wavelength around ∼20 nm due to their relatively low pulse energy.…”
Section: Generation Of Fully Coherent X-ray Pulsesmentioning
confidence: 99%
“…When the temporal coherence of FEL light is determined by the shot noise of an electron beam, as in self-amplified spontaneous emission (SASE), it is poor [13][14][15], but if it is determined by an external seed laser, the FEL light takes on the excellent temporal coherence properties of the external laser in the region that has been seeded. However, if the seed pulse is short while the electron bunch is long, the noisy SASE background signal can overwhelm the seeded radiation, wiping out the benefits of the seed.To reduce this noisy background, the FEL radiator is typically made short enough that the unseeded portion of the bunch does not reach saturation while the seeded portion does, but this can be limited in the case of short seeds with low seed power [1,[5][6][7]. Alternatively, the electron bunch could be made short relative to the seed, but this puts challenging constraints on the synchronization between the femtosecond-scale seed and the electron bunch.…”
mentioning
confidence: 99%
“…To reduce this noisy background, the FEL radiator is typically made short enough that the unseeded portion of the bunch does not reach saturation while the seeded portion does, but this can be limited in the case of short seeds with low seed power [1,[5][6][7]. Alternatively, the electron bunch could be made short relative to the seed, but this puts challenging constraints on the synchronization between the femtosecond-scale seed and the electron bunch.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One option is direct seeding with a coherent source, based on high-harmonic generation (HHG) in gas [20][21][22]. However, this approach is still under development and is currently limited to wavelengths above several tens of nanometers, due to the relatively low efficiency of HHG.…”
Section: Introductionmentioning
confidence: 99%